2006
DOI: 10.4141/a05-009
|View full text |Cite
|
Sign up to set email alerts
|

The responseof plasma leptin and feed intake to growth hormone administration in Holstein calves with different planes of nutrition

Abstract: . 2006. The response of plasma leptin and feed intake to growth hormone administration in Holstein calves with different planes of nutrition. Can. J. Anim. Sci. 86: 225-233. This study was conducted to observe the effect of the growth hormone (GH)/insulin-like growth factor-1(/IGF-1) axis on leptin and feed intake of 15 Holstein calves in three groups. One group was fed a normal diet (control); the second group, with high nutrition after low feeding with bovine growth hormone (bGH), and a third group, without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Leptin concentration increased after 20 days on concentrates in period 2 in the LUC 1 Feedlot treatment, confirming its rapid response to higher feeding levels (Chilliard et al, 1999;Lee et al, 2006). Leptin was correlated with BW as reported in growing bulls by Geary et al (2003) and Bellmann et al (2004), who also found positive correlations between serum leptin and the amount of fat in different deposits.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Leptin concentration increased after 20 days on concentrates in period 2 in the LUC 1 Feedlot treatment, confirming its rapid response to higher feeding levels (Chilliard et al, 1999;Lee et al, 2006). Leptin was correlated with BW as reported in growing bulls by Geary et al (2003) and Bellmann et al (2004), who also found positive correlations between serum leptin and the amount of fat in different deposits.…”
Section: Discussionmentioning
confidence: 60%
“…Changes in this status can alter concentrations of blood metabolites like non-esterified fatty acids (NEFA), which reflect fat mobilization, and hormones such as IGF-I and leptin (Lee et al, 2006). Serum IGF-I concentration is related to nutritional status and protein deposition (Ellenberger et al, 1989;Hornick et al, 2000), while leptin concentration is related to adiposity and feed intake (Chilliard et al, 1999), and therefore they might be useful to predict performance at key moments of the production cycle.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast low leptin in underfed animals can stimulate feed intakes and modulate metabolic responses (Ahima et al, 1996;Friedman and Halaas 1998;Heiman et al, 1998). In calves, Lee et al (2006) showed that leptin concentrations reflect changes in nutritional status in calves of 5 mo, whereas leptin decreases with feed restriction, it increases with refeeding. This could mean that lower leptin concentrations are coupled with hunger, which is consistent with the lower concentrations at weaning (d 56) compared with the ad libitum phase (d 28) in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…This result may be attributed to the increases in voluntary feed intake as DM and TDN (Tables 5 & 6). In addition, GH plays an important role in regulating whole-body energy utilization and well-lipolytic action (Lee et al, 2006). Furthermore, Brian et al (2004) showed that GH had the mechanism to act on an increase in growth rate, feed consumption, and whole-body fat deposition.…”
Section: Discussionmentioning
confidence: 99%